2022
DOI: 10.2147/dddt.s358229
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Herbal Medicine-Based Phytochemical of Garcinia as Molecular Therapy for Breast Cancer

Abstract: Data from globocan statistic in 2020 indicate that breast cancer has become highest incidence rate of cancer. Estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2) are known immunohistochemistry (IHC) markers that mediate cell growth and survival signaling. Furthermore, regulator proteins, receptors, and their downstream signaling pathways have emerged as critical components in breast cancer formation and proliferation, and have become well-established therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…More recently, using the CCK-8 viability assay, the IC 50 of GBA was calculated at 0.4 μg/ml (or 0.64 µM) against the mouse triple negative breast cancer cell line 4T1 and less than 1.0 μg/ml (or less than 1.59 µM) against the MDA-MB-231 cell line (Dang et al, 2021). Overall, our findings corroborate previous studies on GBA and related CGXs indicating a favorable therapeutic index as evidenced by a selective submicromolar cytotoxicity against all breast cancer subtypes with no apparent detrimental effects in normal human breast epithelial cells (Li et al, 2012;Bai et al, 2015;Chantarasriwong et al, 2019;Triyasa et al, 2022).…”
Section: Cytotoxicity Profile Of Gbasupporting
confidence: 89%
“…More recently, using the CCK-8 viability assay, the IC 50 of GBA was calculated at 0.4 μg/ml (or 0.64 µM) against the mouse triple negative breast cancer cell line 4T1 and less than 1.0 μg/ml (or less than 1.59 µM) against the MDA-MB-231 cell line (Dang et al, 2021). Overall, our findings corroborate previous studies on GBA and related CGXs indicating a favorable therapeutic index as evidenced by a selective submicromolar cytotoxicity against all breast cancer subtypes with no apparent detrimental effects in normal human breast epithelial cells (Li et al, 2012;Bai et al, 2015;Chantarasriwong et al, 2019;Triyasa et al, 2022).…”
Section: Cytotoxicity Profile Of Gbasupporting
confidence: 89%
“…Recently, a review article aimed to analyze the potential of Garcinia phytochemicals as a molecular therapy of breast cancer, evaluated the results of 28 article selected studies. The analysis showed that phytochemicals of Garcinia , including garcinol, have anti-cancer properties, resulting from apoptosis, inhibition of proliferation, and metastasis in breast cancer cells [ 75 ]. The mechanisms involved in its anti-cancer effects included the reversal of EMT associated with the upregulation of epithelial marker E-cadherin and downregulation of some mesenchymal markers including vimentin, ZEB1 and ZEB2.…”
Section: Chalcones and Breast Cancermentioning
confidence: 99%
“…Garcinia , taxonomically classified within the Guttiferae or Clusiaceae family, large genus includes 400 species distributed primarily in Africa, tropical Asia and Polynesia. It is a rich sources of medicinal compounds for instance hydroxycitric acid, procyanidines, garcinol, α-mangostin, cambogin, and gambogic acid making this genus a rich repository of useful compounds [ [5] , [6] , [7] , [8] ].…”
Section: Introductionmentioning
confidence: 99%